2022
DOI: 10.3390/cancers14143354
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Optical Coherence Tomography and Optical Coherence Tomography Angiography in the Imaging and Differentiation of Choroidal Melanoma: A Review

Abstract: Choroidal melanoma requires reliable and precise clinical examination and diagnosis to differentiate it from benign choroidal nevi. To achieve accurate diagnosis, as well as monitoring the progression of disease, various imaging modalities are used, including non-invasive optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA). This review begins with a historical account of the development of OCT and OCTA and the methods of generation of images. This outlines the understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Moreover, a synthesis of features discerned via multimodal imaging has been recognized as prognostic of SMCL progression to CM. [3,5,6] The seminal research conducted by Augsburger et al [7] was at the forefront of exploring risk factors in these lesions. Their analysis revealed that certain characteristics, notably a base size exceeding 5 mm, a height greater than 1.5 mm, juxtapapillary location, symptomatology, presence of orange pigment, and subretinal uid, were signi cantly correlated with an augmented risk of lesion growth.…”
Section: Discusionmentioning
confidence: 99%
“…Moreover, a synthesis of features discerned via multimodal imaging has been recognized as prognostic of SMCL progression to CM. [3,5,6] The seminal research conducted by Augsburger et al [7] was at the forefront of exploring risk factors in these lesions. Their analysis revealed that certain characteristics, notably a base size exceeding 5 mm, a height greater than 1.5 mm, juxtapapillary location, symptomatology, presence of orange pigment, and subretinal uid, were signi cantly correlated with an augmented risk of lesion growth.…”
Section: Discusionmentioning
confidence: 99%
“…OCT is a similar method to that of ultrasound, but it uses light instead of sound, and produces images of a higher magnitude (it can deliver images of 1–15 μm contrary to traditional ultrasound techniques which have significantly lesser spatial resolution). 32 34 …”
Section: Optical Coherence Tomography – History and Basic Principlesmentioning
confidence: 99%
“…OCT is a similar method to that of ultrasound, but it uses light instead of sound, and produces images of a higher magnitude (it can deliver images of 1-15 μm contrary to traditional ultrasound techniques which have significantly lesser spatial resolution). [32][33][34] OCT imaging is an important non-invasive technology in the detection and monitoring of glaucomatous structural damage. Over the years, OCT techniques have evolved from time-domain OCT (TD-OCT) to spectral-domain OCT (SD-OCT) and swept-source OCT (SS-OCT), which have improved the resolution and speed of scans.…”
Section: Octmentioning
confidence: 99%
“…Furthermore, optical coherence tomography (OCT) and optical coherence tomography angiography(OCTA) have been used recently to capture superficial and deep retinal and choroidal structures non-invasively, providing more accurate details of the lesion [ 31 ]. Melanomas on OCT reveal serous retinal detachment, normal retinal thickness, debris on back of retina, and intact photoreceptors [ 1 ].…”
Section: Physical Examination and Evaluationmentioning
confidence: 99%